Sabda Raja Sultan Hamengku Buwono X Menurut Aktivis PWNU Yogyakarta Dan Aktivis PWM Yogyakarta: Studi Analisis Terhadap Penghapusan Gelar Khalifatullah - Atiq, Diana Sitatul (UIN Sunan Kalijaga Yogyakarta, 2016)
The Sultanate of Yogyakarta is the legal heir to the Islamic Mataram kingdom with a royal government system that still exists today. In the system of royal government, a Sultan (king) has the highest absolute authority, both in the form of prohibitions and orders. This research is a field research using the interview method with Nahdlatul Ulama activists (PWNU Yogyakarta) and Muhammadiyah activists (PWM Yogyakarta). This research is descriptive analytic in nature, namely an attempt to describe and collect data related to the removal of the title Khalifatullah, then an analysis of the data is carried out based on existing theories in Islamic law. The results showed that Nahdlatul Ulama activists refused to abolish the Khalifatullah title on the grounds that the Khalifatullah title contains al-'urf, and the Khalifatullah title has become a legitimacy and recognition that the line of power in the Palace is based on male offspring. Whereas Muhammadiyah activists refused to abolish the title on the grounds that they were in the leadership of the Keraton, the tradition of changing power was to adhere to a patriarchal system, and the title Khalifatullah was an affirmation that men were the ones who had the right to inherit the leadership of the Keraton. According to the author's analysis, Nahdlatul Ulama activists use the Ijtihad Jamâ'i method, namely in extracting and making decisions related to their rejection of the abolition of the Khalifatullah title by practicing qawa'id ushuliyyâh and qawa'id fiqhiyyâh and through deliberations and in-depth discussions by gathering people who understand the the problems, namely the clergy, government experts and the royal family of the palace. Whereas Muhammadiyah activists use the Al-Ijtihâd al-Istislahi method, which is more based on the illat or benefits obtained.